Marcadores discursivos e tipos de discurso - Coutinho, Maria Antónia (2008)
This article deals with the status of discourse markers, according to different approaches of discourse. In a first moment, we will discuss the distinction between discourse markers and other linguistic forms, often taken as non-discursive. Different proposals, concerning categories and functions of linguistic markers, will then be analysed. Focusing on socio-discursive interactionism theoretical framework, in the third moment we develop the notion of types of discourse, thus providing evidence for different discursive uses, even within the discourse markers’ class. Concluding remarks will point out the convenience of moving from a logical and grammatical point of view to a rhetorical and hermeneutic approach.